Pendidikan Multikultural Di Masyarakat Suku Tengger Tosari Pasuruan (Studi Gerakan Pencerahan Muhammadiyah Tosari Pasuruan) - Luqman Wahyudi (Adabiyah : Jurnal Pendidikan Islam, 2017)
This study aims to: 1) To know how the Multicultural education movement Tengger Tosari Pasuruan people; 2) To know how the development of the Muhammadiyah enlightenment movement in the Tengger Tosari Pasuruan Tribe community; 3) To know how far the contribution of Muhammadiyah movement in the development of Multicultural education in Tengger Tosari Pasuruan people. Qualitative research with phenomenology approach is considered most appropriate to get meaningful data in society Tengger Tosari Pasuruan. Data collection techniques were conducted on natural settings, primary data sources, and more data collection techniques on participant observatioan, in-depth interviews and documentation. Data analysis is done inductively based on facts found in the field and then constructed into hypotheses or theories. From the research results can be concluded that: 1) Multicultural education movement of Tengger Tosari Pasuruan Tenggerese community has been implemented by Tengger Tosari Pasuruan people: 2) The development of the Muhammadiyah enlightenment movement in the Tengger Tosari Pasuruan society so rapidly started in 1922 when KH Ahmad Dahlan Tosari Pasuruan until now, namely enlightenment conducted by PCM Tosari under the leadership of Mr. Anshori; 3) The contribution of the Muhammadiyah movement in the development of Multicultural education is evident from the Muhammadiyah families and the Muhammadiyah figures in Tosari is the spearhead of the implementation of multicultural education. It is also necessary for the implementation of Multicultural education in the formal and non-formal education sector and further research on KH's history and propagation. Ahmad Dahlan in Tosari, because it concerns the history of the Kyai and the history of Muhammadiyah Indonesia in general and Muhammadiyah Tosari Pasuruan in particular.